Ectoparasites of two species of rodents (Gerbilliscus leucogaster and Saccostomus campestris) and the role of host factors and habitat type on ectoparasite diversity and infestations - Smith, Amber Terry (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScConEcol)--Stellenbosch University, 2023.